If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -6 = -12 Reorder the terms: -6 + 3a = -12 Solving -6 + 3a = -12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3a = -12 + 6 Combine like terms: -6 + 6 = 0 0 + 3a = -12 + 6 3a = -12 + 6 Combine like terms: -12 + 6 = -6 3a = -6 Divide each side by '3'. a = -2 Simplifying a = -2
| -23r+79=-13 | | 7n+3=4n+12 | | 7-(x-3)=5(2-x) | | 6x^2+6x=180 | | 3/4*131/3 | | 10k-6=24 | | 185.00+35.00=1 | | .10*x=3500 | | 2A+2B=4C | | -3y-2=7 | | .667w-6=1 | | 3/x-1/4=x/4 | | x*.10=3500 | | 3x-4=100+x | | 12a-10=-250 | | 43w-6=1 | | 5(-4-3k)+8k=-1.3(18+6k)+1 | | 19=3x+7x+9 | | -73=5n+(-8) | | 4/x-1/3=x/6 | | -2r+7(4-6r)=-8(5r-6) | | G+2(8-3G)-2g=1.2(4g-4) | | 0.5x+7=11 | | 417.775/0.025 | | -3x+1=4x-7 | | -9p+24=-246 | | 5e-4(3-2e)=1.2(48e+20) | | 22/3x-11/4=41/3 | | x/8-10=70 | | 5.9+c=3c | | 47/10/32/5=x/2 | | 7-8b=-41 |